Financial Auditing in Education: A Systematic Review of Practices, Challenges, and Policy Recommendations - Sudirman, Irmayanti; Tijjang, Bakhtiar; Machmud, Mulyana; Modding, Basri; Safrida; Putra, Pandi (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Financial audits in the education sector ensure transparency, accountability, and efficiency in using budgets. This article examines financial audit practices in the education sector and the challenges faced in their implementation. Using the Systematic Literature Review (SLR) approach and the PRISMA method, we analyzed various studies that discussed audits in educational institutions, from primary schools to colleges. The results of this review show that although financial audits have been widely implemented, various challenges still hinder their effectiveness. These challenges include limited competent human resources, regulatory complexity, and uncertainty in financial reporting. On the other hand, best practices such as using more advanced audit technology and ongoing financial audit training have proven to improve audit quality. The article also identifies the need for policy reforms that support transparency and improve the competence of auditors in the education sector. Effective financial audits in education require synergy between policies, regulations, and professional practices.